Hardware Hacking: An Approach to Trustable Computing Systems Security Education (Journal of The Colloquium for Information Systems Security Education, 2015)
Traditional approaches to teaching computer security have focused on understanding software and network security. However, computer systems comprise not only software and networks, but also include hardware components. The security of computer systems hardware has been typically ignored in most computer security curricula. In this paper, we describe a set of courses that can form a core of a hardware security curriculum. We pay particular emphasis to a “hardware hacking” class where students are exposed to a variety of hands-on exercises with hardware assurance. The class has shown that it not only introduce students to the topics of hardware assurance but also improve their hardware and digital design skills as well.